The concept of peace region as alternative to (traditional) political autonomy - Brousek, Jan (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2018)
The point of departure are experiences from a dialogue project aimed to contribute to the development of a Peace Region Alps-Adriatic (PRAA) by attempts to reveal and overcome the deep-rooted historic conflict lines between the various minority and majority populations in that specific geographical area. Such a concept of peace region can prove a strategy for the inclusion and integration of national minorities. It can reduce secessionist tendencies by establishing a framework which serves as an alternative to (traditional forms of) autonomy. The task of such a framework of a peace region is to enable the coexistence of autonomous or alternative (historical) narratives to the dominant (nation-based) mainstream narrative(s). By doing so, the concept of peace region can also act as a basis for the realization of further economic and political crossborder cooperation.
Keywords: avtonomija; dialog; integracija; Mirovna regija Alpe-Jadran; mirovne pobude; narodne manjšine